PERAN KECAMATAN BANTAR GEBANG DALAM MENDUKUNG KETAHANAN PANGAN BERAS KOTA BEKASI - Mochtar Cahyo Utomo (Universitas Gadjah Mada, 2013)
This paper explained the district’s role to fulfilled the rice’s need in the region. The quantitative data showed rice food resilience Bekasi and Bantargebang District had not yet fulfilled. The rice availability which came from the internal rice production source, Bekasi contribution (1.05%), and Bantargebang District (3.86%) was very low therefore the dependence on external rice production was very high (more than 96%) however the rice production source was only on the average Bekasi contribution (126.77%) and Bantargebang District (36.43%). However the distribution and access aspect of rice consumption had been well fulfilled. Bantargebang District’s role as the district with the largest paddy field had not yet given a meaningful contribution to the Bekasi internal rice production.Keywords: District’s Role, Rice Production, Food Resilience.